From crisis to control: The revival of Banco di Napoli's land credit under the management of Nicola Miraglia - Mattia Muscherà (The Journal of European Economic History (JEEH), 2025)
This paper examines the pivotal role of Nicola Miraglia in steering the Banco di Napoli through a tumultuous period of economic crisis and institutional decay in the late 19th and early 20th centuries. Miraglia undertook the daunting task of managing a bank on the brink of bankruptcy due to the aftermath of the 1893 banking crisis and the Banca Romana scandal and implemented a series of strategic reforms focused on careful management and asset liquidation. Utilizing archival data from the Banco di Napoli's Historical Archive, Fondo Miraglia, the paper analyses the administrative and financial performance of the Neapolitan institute under Miraglia's leadership. Highlighting the successful transition of the Land Credit into a phase of liquidation, characterized by improved revenue streams and meticulous debt management. Tables detailing variations in administration building costs and development of building rents across different cities underscore the positive impact of Miraglia's reforms. Ultimately, the paper concludes that Miraglia's leadership played a crucial role in stabilizing and revitalizing the Banco di Napoli, setting it on a path towards recovery and long-term sustainability. His perseverance, competence, and moral integrity were instrumental in addressing the complex issues plaguing the Banco and laying the groundwork for its continued operations during a period marked by economic volatility and institutional uncertainty.
Keywords: 330; Bank; Bankmanager; Bankenkrise; Unternehmenssanierung; Unternehmensgeschichte; Neapel; Italien